The effect of plasma treatment on the osseointegration of rough titanium implant: A histo-morphometric study in rabbits - Wan-Ching Chou; Rex C.-C. Wang; Chih-Ling Huang; Tzer-Min Lee (Elsevier, 2018)
Abstract Background/purpose: The surface properties, such as hydrophilicity and functional OH groups, play an important role in bone fixation in vivo. In our previous study, the plasma treatments of large grit and acid etching (SLA) method produce functional OH groups on the rough surface. There is no report in discussing the integration between basic TiOH groups and bone-to-implant contact (BIC). The aim of this study was to evaluate the effect of the functional OH groups on the rough surface both in vitro and in vivo. Materials and methods: Functional hydroxyl groups were produced on a SLA-treated surface. The surface topography, roughness, wettability, and chemical composition were examined using various techniques. Twenty-four implants were inserted into the proximal tibia of four New Zealand white rabbits. The biological responses were measured in terms of histomorphometric analysis 4 and 8 weeks post-implantation. Results: The surface morphology and roughness were similar among all groups. However, the concentration of OH groups and hydrophilicity were found increased in the plasma treatment. The cell morphology in RF-plasma treated groups had more polygonal type and higher expression of actin and vinculin. The bone-to-implant contact (BIC) ratios of RF-200W were significantly higher than other groups (P < 0.05). The relationship between basic OH groups and BIC showed linear correspondence. Conclusion: The TiOH groups introduced on the rough surface by plasma treatments can trigger cell adhesion which further initiate new bone apposition. We propose that RF-plasma treatment can help to enhance bone healing at 4 and 8 weeks. Keywords: Hydrophilicity, Functional OH groups, Plasma treatment, Bone-to-implant contact